Professional Dispositions of Teacher Candidates: Measuring Dispositions at a Large Teacher Preparation University to Meet National Standards. Issue 2 (9th September 2020) - Saltis, Michelle N.; Giancaterino, Brea; Pierce, Corey
Abstract: The current study reports the process by which one of the largest teacher preparation institutions in the Western U.S. assesses teacher candidates' professional dispositions throughout their teacher preparation programs through the use of a survey developed by the university. The survey is completed by teacher candidates, mentor teachers, and supervising faculty. Results were analyzed using a Generalized Estimated Equations Model. Results indicated a slight increase in mean scores over time and mentor teachers rated students higher than the students rated themselves. No significant difference in mean scores was found between teacher candidates and supervising faculty. Reliability and validity of the instrument and results are discussed. Lastly, implications for the use of the Professional Dispositions Qualities (PDQ) instrument for accreditation purposes are discussed.